THE EFFECT OF SUBSTRATE CONCENTRATION AND MOLE DOSAGE (LOCAL MICROORGANISM) KOHE CATTLE ON PLANT GROWTH AND PRODUCTION REMOVED SPAIN (Amaranthus tricolor.) - achmad febri; Djuhari Djuhari; Siti Muslikah (AGRONISMA, 2022)
The purpose of this study was to determine the influence of a substrate concentration with a MOL dose of cow kohe on the growth and yield of plucked spinach plants. Between March and May 2021, this research was conducted in Randuagung Village, RT 06 RW 05 Gondang Tengah, Singosari District, Malang Regency. At an elevation of 487 meters above sea level, the average air temperature ranges between 22ËšC-32ËšC. This study used a factorial randomised block design with two components; the first factor is the substrate concentration, which is available in four concentrations (20%, 30%, 40%, and 50%). Simultaneously, the second factor is the MOL dose, which is classified into three levels: Â½ recommended dose (20 lt/Ha), 1 recommended dose (40 lt/Ha), and 1.5 recommended dose (60 lt/Ha). Each combination of treatments is repeated up to three times. The variables analyzed were the height of the plant, the number of leaves, the diameter of the stem, the area of the leaves, the fresh root weight, the root length, the total fresh weight, and the fresh economic weight. The results indicated that the application of a 40% substrate concentration and a 20 l/ha MOL dose of cow kohe had an interaction effect on the growth of plucked spinach plants, as evidenced by plant height variable data (77.50 cm)